Kidney Enlargement Suppression by Cinacalcet In ADPKD Patient With Hemodialysis: A Case Report - Nakatani, Shinya; Mori, Katsuhito; Okuno, Senji; Nishide, Kozo; Morioka, Fumiyuki; Machiba, Yuri; Uedono, Hideki; Tsuda, Akihiro; Ishimura, Eiji; Shoji, Shigeichi; Yamakawa, Tomoyuki; Inaba, Masaaki; et al. (Archives of Clinical and Medical Case Reports, 2020)
Autosomal dominant polycystic kidney disease (ADPKD) is a common type of inherited kidney disease and the fourth leading cause of end-stage renal disease (ESRD). A massively enlarged kidney can impact quality of life, thus volume reduction interventions including transcatheter arterial embolization are generally performed. Although those are effective, several clinical problems such as bleeding, severe pain, or fever can develop. Thus, an effective safe therapy for suppressing progression of kidney enlargement for ESRD patients with ADPKD is desired. A 51- year old male with ADPKD began hemodialysis in 2000. However, total kidney volume (TKV) continued to increase from 2937 mL in February 2006 to 3652 mL in February 2008. For secondary hyperparathyroidism as reflected by serum intact parathyroid hormone level at 370 pg/mL, cinacalcet, an allosteric modulator of the calcium-sensing receptor, was started at the daily dose of 25 mg on February 18, 2008. During 1-year of cinacalcet treatment, TKV remained unchanged at 3189 mL on January 30, 2009, although, with its discontinuation for one year thereafter, TKV exhibited a remarkable increase to 3729 mL on January 26, 2010. Cinacalcet-related hypocalcemia was not noted because serum calcium level was controlled with an intravenous vitamin D receptor agonist and calcium-containing phosphate binders. Findings in this case suggest a novel and potential therapeutic effect of cinacalcet to suppress kidney enlargement in ADPKD patients.